High-Resolution Detection of Loss of Heterozygosity of Dinucleotide Microsatellite Markers. (February 2001) - Hourihan, Rebecca N.; O'Sullivan, Gerald C.; Morgan, John G.
Dinucleotide microsatellite markers are frequently investigated to study inheritance, genetic stability, and allele frequency distribution in a wide variety of genetic disorders. Previous studies have encountered significant problems regarding resolution and detection of dinucleotide microsatellites. In this study, a useful method to investigate loss of heterozygosity (LOH) of dinucleotide microsatellite markers is described that involves the use of nondenaturing (Spreadex ® ) submerged gel electrophoresis and SYBR ® Green I nucleic acid staining. This method omits the gel casting step and the use of hazardous radioactive materials frequently used in many microsatellite studies that employ polyacrylamide gel nucleic acid denaturation analysis. Using this method, 62 patients' paired tumor and normal samples were investigated to detect allele deletions in a region of chromosome 7q31.1, which is believed to harbor a tumor suppressor gene. Interpretable results were obtained in all cases. These results were compared to those attained using ABI Prism ™ Genetic Analyzer 310 and GeneScan ® . There were no discrepancies in results obtained between the two assays. The Spreadex system is cheap, does not require larger equipment costs, and may prove to be a useful system for high-throughput investigation of microsatellites. It may have diagnostic significance and also prove useful if applied to population-based genomic screening and linkage analysis.